Politik Hukum Pemberlakuan Undang-Undang Nomor 1 Tahun 2025 terkait Ketentuan yang Memisahkan Kerugian pada Badan Pengelola Investasi Daya Anagata Nusantara (Danantara Indonesia) dan Kerugian Badan Usaha Milik Negara sebagai Kerugian Negara - Fakhrul Ardiyan; Riski Ari Wibowo; Afandono Cahyo Putranto (Jurnal Riset Multidisiplin Edukasi, 2025)
Law No. 1 of 2025 introduces several legal issues, including those related to the establishment of the BPI Danantara (Danantara Indonesia) as a superholding that consolidates the assets of state-owned enterprises (BUMN) within the framework of a sovereign wealth fund. However, it is exempted from being subject to state administration, finance, and state losses, and weakens the oversight mechanism of the Financial Audit Agency of the Republic of Indonesia (BPK RI), which is entrusted with the authority to audit state finances under Article 23E of the 1945 Constitution. These conditions raise concerns about potential governance deviations due to conflicts with the Anti-Corruption Law, the State Finance Law, and the State Administration Law. In this regard, this study analyzes the legal policy direction of the Government through Law No. 1 of 2025 and whether the losses of Danantara Indonesia and BUMN still constitute state losses, thereby allowing Law Enforcement Agencies to continue addressing corruption offenses within BUMN. The analysis shows that the legal policy direction of the Government through the BUMN Law is aimed at shifting the management of BUMN from a centralistic and bureaucratic model to a more decentralized one. This shift aims to improve the investment climate and ease of doing business, ultimately increasing foreign investor interest in placing investments or Foreign Direct Investments (FDI) in Indonesia. However, this has sparked both support and opposition due to the vulnerability to corruption practices within BUMN. Despite this, based on the principle of lex specialis derogat legi generali and Articles 2 and 3 of the Anti-Corruption Law, the losses from Danantara Indonesia and BUMN remain considered state losses, provided there is an unlawful act, such as corruption, embezzlement of funds, or fraud in the management of investments that leads to state losses.